SEMINAR KOMUNIKASI EFEKTIF DALAM MENINGKATKAN INTERAKSI SEHAT DI RUMAH SAKIT DAERAH DADI - Ismail, Ismalandari; Mukhlis, Andi Mukrim; Ayu, Annisa Putri; Ramadhani, Aulia Zahrah; Azzahra, Chici Firdha; Ramadhana, Muhammad Ismul Azham (LPPM Institut Pendidikan Nusantara Global, 2022)
Communication is important to maintain relationships, especially in the work environment. However, based on preliminary data conducted at the Rumah Sakit Khusus Daerah Dadi (RSKD) in South Sulawesi Province, there is still a lack of knowledge about communication and how to make communication more effective. The purpose of this activity is to provide knowledge and effective communication skills to the staff and employees at Rumah Sakit Khusus Daerah Dadi. The methods used are lecturing and sharing sessions. The participants consist of 41 participants, 9 of whom were male, while 32 participants were female registered. The result of the seminar shows that the activity runs well. It can be known from the improvement of the post-test conducted by the participants after following the seminar.